THU0300 Network meta-analysis of tofacitinib vs bdmards or apremilast for the treatment of tnf inhibitor-naÏve patients with psoriatic arthritis. (12th June 2018) - Gladman, D.D.; Orbai, A.-M.; Gomez-Reino, J.; Chang-Douglass, S.; Leoncini, E.; Burton, H.E.; Kanik, K.S.; Hendrikx, T.; Cappelleri, J.C.; Hsu, M.-A.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of psoriatic arthritis (PsA). Objectives: To perform a systematic literature review (SLR) and network meta-analysis (NMA) to evaluate the efficacy of tofacitinib 5 and 10 mg BID relative to biologic disease-modifying antirheumatic drugs (bDMARDs) or a targeted synthetic DMARD (apremilast [APR]) in tumour necrosis factor inhibitor-naïve (TNFi-N) patients with active PsA. Methods: The SLR identified randomised controlled clinical trials (RCTs) evaluating tofacitinib, bDMARDs or APR to treat patients with active PsA who were TNFi-N. Outcomes included American College of Rheumatology (ACR)20 response and change from baseline in Health Assessment Questionnaire-Disability Index (ΔHAQ-DI), Dactylitis Severity Score (ΔDSS) and Leeds Enthesitis Index (ΔLEI). Treatment effects were only evaluated during placebo (PBO)-controlled trial phases. The Bayesian NMA (with non-informative priors) was conducted using WinBUGs. The binomial logit model was used for ACR20. ΔHAQ-DI, ΔDSS and ΔLEI were analysed using the normal identify link model. A fixed-effect model was fitted to the data. Median treatment rankings represent data from each iteration of the model from which inferences are based, following model convergence. Results: The SLR identified 25 RCTs and 21 were included in the NMA (see treatments in table 1). All trials allowed methotrexate use. PBO-controlled treatment durations ranged from 12–24 weeks. In general, patient characteristics were similar across trials. All treatments were associated with improvements in ACR20 and ΔHAQ-DI vs PBO. Tofacitinib 5 mg BID was associated with substantially decreased odds ratios (ORs) for ACR20 vs golimumab 50 and 100 mg Q4W, etanercept 25 mg BW, infliximab 5 mg/kg and secukinumab 150 mg QW-Q4W (table 1); ORs for all remaining comparators were not substantially different. Tofacitinib 10 mg BID was associated with a substantially increased OR for ACR20 vs APR 20 mg BID. Etanercept was associated with an improvement in ΔHAQ-DI vs tofacitinib 5 and 10 mg BID. There was no difference in ΔHAQ-DI for tofacitinib vs other bDMARDs. For ACR20, tofacitinib 5 and 10 mg BID were median ranked 14 (95% credible interval: 8, 17) and 9, 5, 14 respectively, among 18 comparators. For ΔHAQ-DI, tofacitinib 5 and 10 mg BID were median ranked 11 4, 13 and 8, 2, 13 respectively, among 14 comparators. Two studies evaluated ΔDSS and ΔLEI; there were no substantial differences in ΔDSS and ΔLEI for tofacitinib 5 and 10 mg BID vs adalimumab 40 mg Q2W and ixekizumab 80 mg Q2W and Q4W. Conclusions: Based on the NMA of published RCTs in TNFi-N patients with PsA, tofacitinib 5 and 10 mg BID had similar efficacy vs many, but not all, bDMARDs and APR in improving ACR20 and ΔHAQ-DI. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by P Scutt of CMC and funded by Pfizer Inc. Disclosure of Interest: D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, A.-M. Orbai Grant/research support from: Celgene, Eli Lilly, Horizon, Janssen, Novartis, Pfizer Inc, UCB, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, J. Gomez-Reino Grant/research support from: AbbVie, MSD, Pfizer Inc, Roche, Consultant for: Pfizer Inc, Speakers bureau: AbbVie, Biogen, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc and Roche, S. Chang-Douglass Employee of: Decision Resources Group, E. Leoncini Employee of: Decision Resources Group, H. Burton Employee of: Decision Resources Group, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M.-A. Hsu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc